Updates from a single-center phase 2 study of PD-1 inhibitor combined with hypomethylating agent plus CAG regimen in patients with relapsed/refractory acute myeloid leukemia - Zhou, Hui-Sheng; Su, Yong-Feng; Wang, Jun; Hu, Ya-Lei; Wang, An; Xu, Lei; Wang, Yi-Zhi; Zheng, Xuan; Li, Yu-Qing; Min, Kai-Li; Gao, Chun-Ji; Liu, Dai-Hong; et al. (Frontiers in Immunology, 2025)
IntroductionAnti-PD-1 monotherapy has shown limited clinical efficacy in patients with relapsed/refractory acute myeloid leukemia (r/r AML). Our study aimed to analyze the effectiveness and safety of combining tislelizumab with a hypomethylating agent (HMA) plus CAG regimen in treating patients with r/r AML, with an increased sample size and in comparison, with a historical control group for more reliable data support (ClinicalTrials.gov identifier NCT04541277).MethodsThe study included a total of 37 patients with r/r AML who received the tislelizumab + HMA + CAG regimen.ResultsThe overall response rate was 69.4%, with a median overall survival of 12.1 months and event-free survival of 6.2 months. Multivariate analysis revealed that patients aged 40 or above exhibited a higher response rate, while those with lower leukemia burden (bone marrow blast percentage <40%) demonstrated improved overall survival and event-free survival. Additionally, bridging allogeneic hematopoietic stem cell transplantation was associated with extended event-free survival. Grade 2-3 immune-related adverse events were observed in 8.5% of patients, and no deaths were directly attributed to these events. After propensity score matching, the inclusion of tislelizumab appeared to positively influence the overall response rate and event-free survival compared to historical controls treated with HMA + CAG regimen.DiscussionOverall, the combination regimen improved response rates while maintaining low incidence and severity of immune-related adverse events for r/r AML patients.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT04541277.